FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Diah Rahmawati; Nur Diana (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this study is to find out how the influence of investmentdecisions, dividend policy and financing decisions on the value of manufacturingcompanies listed on the Indonesia Stock Exchange (IDX) period 2014-2016.Technique of data retrieval in this research use purposive sampling method andobtained 29 sample company that used in criterion of manufacturing companylisted in Bursa Efek Indonesia year 2014-2016. Source of data in this researchcomes from Indonesia Stock Exchange (BEI). The method of analysis used in thisstudy is the normality test, the classical assumption test, hypothesis test andmultiple linear analysis.The results of this study indicate that: (1) Based on the simultaneous test orF test it is known that the investment decision variables, dividend policy andfunding decision have a significant positive effect on the value of the company. (2)The variables of investment decision, dividend policy, and funding decisiontogether have 58.8% implication on the value of the company in manufacturingcompanies listed on BEI and 41.2% are explained by other variables not includedin the research model. (3) Partially, investment decision variable and fundingdecision have a significant positive influence to firm value while dividend policyvariable does not affect to company value.Keywords : Investment Decisions, Dividend Policy, Funding Decision, CorporateValue.